Geology of Ceres’ North Pole quadrangle with Dawn FC imaging data - Ruesch, O.; McFadden, L.A.; Williams, D.A.; Hughson, K.; Paschkert, J.H.; Scully, J.E.C.; Kneissl, T.; Roatsch, Thomas; Nass, Andrea; Preusker, Frank; Schmedemann, N.; Marchi, S.; et al. (Icarus, 2018)
The Dawn Framing Camera repeatedly imaged Ceres’ North Pole quadrangle (Ac-1 Asari, latitudes >66°N) at a resolution of ∼35 m/pixel through a panchromatic filter, enabling the derivation of a digital terrain model (DTM) and an ortho-rectified mosaic. Using this dataset, a photo-geologic map and stratigraphy, complemented with absolute model ages of impact craters, were produced. We identified the following key surface features: an ancient 4.5 km high isolated dome with a non-impact origin; recent lobate materials on crater interiors possibly formed as high-speed flows of collapsed rim material; and recent bright areas in permanently shadowed regions (PSRs), which we interpret as ice accumulation mostly by infall of exogenic material. Crater morphologies and dimensions do not differ from those in other quadrangles, suggesting the widespread influence of a rheologically weak target during the crater formation process. There is a paucity of lobate materials associated with impact cratering, in contrast to previous identifications with lower spatial resolution imagery.